The Evaluation of Sales Accounting Information System Using Pieces Method at Kelana Scarves Shop - Miftahul Jannah Dondo; Yuniarti Hidayah Suyoso Putra (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
Every company is required to maximize existing resources in carrying out the company's activities effectively and efficiently. Therefore, companies need an accounting information system that can support the supervision of various operational activities well. This research aims to evaluate the sales accounting information system applied by the Kelana Scarves Shop using the PIECES (Performance, Information, Economy, Control, Eficiency dan Service) analysis method. The research used descriptive qualitative research with a case study approach. The data collection techniques include observation, interview, and documentation. The data analysis uses data reduction, data presentation, and analysis using the PIECES method. According to the PIECES method, the results show that the users are satisfied with using the Olsera POS system. However, the results also indicate there is still a double job in terms of efficiency related to assigning tasks and responsibilities. There is still no optimal service to consumers in the service aspect because the employee ignores the updated information of inventory in the marketplace and the warehouse. Therefore, they can disappoint consumers who want to buy the needed goods